Should Equity Be a Goal of Economic Policy?. (Economic Issues; Economic Issues ;, 1999)
Over the past decade, global output has grown by more than 3 percent a year and inflation has slowed in most regions. The fruits of this growthhave not been shared equally, however, and income disparities have grownin many countries, developed as well as developing. One of the mostpressing issues facing policymakers today is how to respond to these trends. To what extent are growth and equity complementary, and to whatextent is there a trade-off between the two? This Economic Issue is a summary version of an Issues Paper circulated at the IMF Conference on Economic Policy and Equity, held on June 8-9, 1998, at IMF headquarters.